2021
DOI: 10.1002/jgt.22711
|View full text |Cite
|
Sign up to set email alerts
|

Domination versus independent domination in regular graphs

Abstract: A set S of vertices in a graph G is a dominating set if every vertex of G is in S or is adjacent to a vertex in S. If, in addition, S is an independent set, then S is an independent dominating set. The domination number γ G ( ) of G is the minimum cardinality of a dominating

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Babikir and Henning [3] showed that the statement of Goddard et al in the previous paragraph also holds for k-regular graphs when ∈ k {4, 5, 6}. Very recently, Knor, Škrekovski, and Tepeh [12] generalized the result to all ≥ k 3; namely, it is now known that for all…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Babikir and Henning [3] showed that the statement of Goddard et al in the previous paragraph also holds for k-regular graphs when ∈ k {4, 5, 6}. Very recently, Knor, Škrekovski, and Tepeh [12] generalized the result to all ≥ k 3; namely, it is now known that for all…”
Section: Introductionmentioning
confidence: 84%
“…Babikir and Henning [3] showed that the statement of Goddard et al in the previous paragraph also holds for k $k$‐regular graphs when k{4,5,6} $k\in \{4,5,6\}$. Very recently, Knor, Škrekovski, and Tepeh [12] generalized the result to all k3 $k\ge 3$; namely, it is now known that for all k3 $k\ge 3$, if G $G$ is a connected k $k$‐regular graph, then i(G)γ(G)k2 $\frac{i(G)}{\gamma (G)}\le \frac{k}{2}$, and equality holds if and only if G=Kk,k $G={K}_{k,k}$.…”
Section: Introductionmentioning
confidence: 98%